2008
DOI: 10.1007/s10535-008-0012-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pb ions on superoxide dismutase and catalase activities in leaves of pea plants grown in high and low irradiance

Abstract: The role of irradiance on the activity of antioxidant enzymes: superoxide dismutase (SOD) and catalase (CAT) was examined in the leaves of Pisum sativum L. plants grown under low (LL) or high (HL) irradiance (PPFD 50 or 600 μmol m -2 s -1 ) and exposed after detachment to 5 mM Pb (NO 3 ) 2 for 24 h. The activities of both enzymes increased in response to LL compared with HL and no effect of Pb ions was observed. Photosystem (PS) 1 and PS 2 activities were also investigated in chloroplasts isolated from these l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…In the PSII reaction center, Pb interferes mainly with Chl a molecules, impairing their function by the substitution of Mg 2+ ions in porphyrin rings [57], leading to their constant excitation, and thus permanent inactivation of RC [58]. As we mentioned earlier, content of chlorophylls decreased only in Plumbago shoots treated with the high lead concentration.…”
Section: Discussionmentioning
confidence: 60%
“…In the PSII reaction center, Pb interferes mainly with Chl a molecules, impairing their function by the substitution of Mg 2+ ions in porphyrin rings [57], leading to their constant excitation, and thus permanent inactivation of RC [58]. As we mentioned earlier, content of chlorophylls decreased only in Plumbago shoots treated with the high lead concentration.…”
Section: Discussionmentioning
confidence: 60%
“…We previously observed [14] that Pb ions stimulated the respiration rate in pea leaves in plants grown in high light conditions, which was accompanied by an increase in ATP production in mitochondria. We also found that the inhibition of photosynthesis by Pb ions was higher in low-than in high-light-grown plants as a consequence of decreasing electron transport in the photosynthesis light reaction [68]. Lead is absorbed by plants mainly through the root system and in minor amounts through the leaves.…”
Section: Discussionmentioning
confidence: 72%
“…Effect of Cd on C. comosum growth As a non-essential and toxic heavy metal element for plants, Cd can affect mitosis in plant cells, slow the rate of cell division, and influence plant growth by affecting physiological and biochemical processes (Romanowska et al 2008;Seregin and Kozhevnikova 2006). The root system is the main part that absorbs and excludes heavy metals; the root length of sensitive plants are obviously inhibited under heavy metal force while the growth of roots are affected slightly in tolerant plants, so TI is an important indicator that reflects the heavy metal tolerance of plants (Yan et al 1997(Yan et al , 2009.…”
Section: Resultsmentioning
confidence: 99%